The Effect of Google Search Volume Index on Underpriced IPOs and Divergence of Opinions - Megen Chivianti; Sukmawati Sukamulja (Journal of Indonesian Economy and Business (JIEB), 2021)
Introduction/Main Objectives: The purpose of this paper is to examine the effect of the Google Search Volume Index (GSVI), as the moderating variable, on underpriced IPOs, as the independent variable, on the divergence of opinions, as the dependent variable. Background Problems: A divergence of opinions may arise when an error occurs while estimating the right price due to the unavailability of information or only having limited information. Before a company conducts an IPO, potential investors will look for information about the company and each one may interpret the data differently, which results in disagreements between the investors. The investors’ attention is a disagreement mechanism. Research Methods: This study employs the regression analysis of moderation variables with an absolute difference method (ADM) on a sample of 79 Indonesian companies that conducted an IPO between 2015 and 2019. Finding/Results: This study discovered a negative relationship between the initial return and market-adjusted turnover without an interaction effect in the model. The investors’ attention reduces disagreements about underpriced IPOs in the aftermarket. Conclusion: The result of this study found that investors’ attention reduces disagreements about underpriced IPOs proxied by the initial return, because investors closely monitor other information available on the Internet.